(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The increasing integration of power electronic devices in electrical power systems has intensified the need for effective control techniques capable of minimizing transformer transient disturbances in series voltage compensation applications. This study investigates and compares the performance of Pulse Width Modulation (PWM) and Space Vector Pulse Width Modulation (SVPWM) techniques in controlling transformer transients and improving overall compensation system performance. The analysis focuses on critical parameters such as transient response characteristics, harmonic distortion, voltage stability, switching efficiency, and power quality enhancement. A detailed simulation model of a transformer-based series voltage compensator is developed using MATLAB/Simulink to evaluate the operational behaviour of both modulation strategies under different loading and disturbance conditions. The comparative results indicate that the SVPWM technique achieves improved voltage utilization, faster dynamic response, and reduced Total Harmonic Distortion (THD) when compared with conventional PWM methods. In contrast, PWM demonstrates easier implementation and reduced computational requirements, which may be advantageous in less complex applications. The research further highlights the influence of modulation strategies on transformer stress reduction and transient mitigation within modern compensation systems. The outcomes of this work provide a useful reference for the design and optimization of efficient series voltage compensation systems aimed at enhancing power system reliability, stability, and power quality.